The Discourse Referred To In Chronicles On Ecuadorian Migration: Materials For A Heterogeneous Narration - Guaño Arias, Stephanie (2025)
Studies on the Latin American chronicle focus on two moments: modernist chronicle and contemporary production. According to Darrigrandi (2013), the latter shows a special concern for including the experiences and testimonies of those who go through situations of vulnerability or have been marked with stereotypes. In this sense, the migratory experience of Ecuadorians has provoked the interest of chroniclers, whose productions articulate the discourses of migrants in a text that does not lose aesthetic concern nor is obliged to hide personal opinion. Within this framework, the objective of this research is to analyze the treatment of testimonial sources in chronicles on Ecuadorian migration. To this end, it considers the concept of enunciative heterogeneity and the discursive strategies with which the testimony of the source subject is referred to in the text. The corpus of this research is made up of 25 chronicles from 2 compilations published between 2013 and 2016: El color de los sueños: historias de migrantes, by Anabel Chimbo Barros (2016) and Permiso de Residencia, crónicas de la migración ecuatoriana a España, by María Fernanda Ampuero (2013). The results show that the chronicles are a polyphonic discourse that uses direct, indirect citation styles to weave a plot capable of recontextualizing, emphasizing or nuancing the discourse of the source subject.